치위생과 학생의 이론 강의와 동영상 교육 방법에 따른 방사선안전관리 교육의 효과 - 정영희(Young-Hee Jeong); 윤정애(Jung-Ae Yoon) (한국구강보건과학회지, 2019)
Objectives: This study aims to promote dental hygiene students’ awareness of radiation exposure through radiation safety management (RSM) education using theoretical lectures and visual-auditory material. Methods: The subjects were 105 dental hygiene students who took a questionnaire survey between March 25 and May 10, 2019. Results: Examining the knowledge levels of two groups indicated that the average correctness rate of knowledge before training with the theoretical lecture and visual-auditory material was 44.69% and 31.50%, respectively, and that after training was 58.77% and 44.18%, respectively; these differences were statistically significant (t = 0.335, p = .013). The attitude levels of the two groups before training with the theoretical lecture and visual-auditory material gave scores 4.13±.85 and 4.00±.39 points, respectively, and those after training were 4.11±.07 and 3.98±.80 points, respectively; these differences were not statistically significant (t = 0.037, p = .008). Further, the radiation anxiety score before training with the theoretical lecture and visual-auditory material was 3.11±.73 and 2.97±.54, respectively, and that after training was 3.13±.83 and 2.76±.56, respectively; these differences were not statistically significant (t = 1.215). The knowledge score showed a statistically positive correlation with the radiation hazard anxiety score (r = .229, p = .019). Conclusions: We believe that a variety of programs should be offered to dental hygiene students to provide knowledge on RSM as a prerequisite for improving their level of RSM. KCI Citation Count: 3